Pharmacological rescue of the G85E CFTR variant by preclinical and approved modulators - Tomati, Valeria; Capurro, Valeria; Pesce, Emanuela; Pastorino, Cristina; Sondo, Elvira; Lena, Mariateresa; Borrelli, Anna; Cresta, Federico; Pantano, Stefano; Collini, Francesca; Ripani, Pietro; Terlizzi, Vito; et al. (Frontiers in Pharmacology, 2024)
Cystic Fibrosis (CF) is a genetic disease due to loss-of-function mutations of the CFTR channel. F508del is the most frequent mutation (70% of alleles in Italy), while other mutations have much lower frequency. Among them, G85E (0.4 % frequency globally, 1.13 % in Italy) emerges as a mutation characterized by a severe CFTR folding and trafficking defect. To investigate the pharmacological responsiveness of the G85E-CFTR variant, we performed a functional and biochemical characterization in heterologous expression systems and ex vivo models based on patient-derived human nasal epithelial cells (HNEC). Our study demonstrated that treatment of primary airway cells with elexacaftor and tezacaftor causes a significant (although modest) rescue of CFTR function, that reaches 15-25% of the activity measured in non-CF epithelia. A detrimental effect of chronic treatment with ivacaftor, further limiting G85E rescue, was also observed. A higher rescue of CFTR function, up to 25-35% of the normal CFTR activity, with no evidence of negative effects upon chronic potentiator treatment, can be achieved by combining elexacaftor with ARN23765, a novel type 1 corrector endowed with very high potency. Importantly, dose-response relationships suggest that G85E might alter the binding of type 1 correctors, possibly affecting their affinity for the target. In conclusion, our studies suggest that novel combinations of modulators, endowed with higher efficacy leading to increased rescue of G85E-CFTR, are needed to improve the clinical benefit in patients for this variant.